User Requirements Analysis of Digital-Based Solutions for Supporting Disabilities using User Journey Map (Case Study of PSLD Brawijaya University) - Rahmah, Yusriyah; Aknuranda, Ismiarta; Ratnawati, Dian Eka (Faculty of Computer Science (FILKOM) Brawijaya University, 2022)
Disability is any condition of the body or mind that makes it more difficult for the person with the condition to do certain activities and interact with the world around them. Persons with disabilities need assistance in various fields related to their limitations to improve their quality of life. Either area that needs to be optimized to fulfill the rights of persons with disabilities is inclusive education. Brawijaya University supports inclusive education by establishing an organizational institution called Pusat Studi dan Layanan Disabilitas Universitas Brawijaya (PSLD UB). PSLD UB provides peer tutoring services by involving non-disabled students (volunteers) to assist students with disabilities during academic activities. So far, the process of implementing peer tutoring has often encountered problems due to schedule changes or other unexpected activities, causing schedule mismatches between volunteers and students with disabilities. To fulfill disability rights, it’s necessary to have a digital solution in peer tutoring activities, while to design the solution it’s necessary to analyze the right user requirements. Therefore, the purpose of this research is to analyze user requirements to optimize user experience, so that developers can use it to develop peer tutoring systems. This study applies a User Journey Map to analyze user requirements to know the description of the user's steps in achieving the goal. The selection of respondents was based on purposive sampling technique with the criteria of respondents who had carried out the peer tutoring process. From the results of this study, it was found three main features that suit user requirements are automatic replacement, emergency requests, and list of available volunteers.